Range Of Motion (ROM) on Muscle Strength in Stroke Patients : Literature Review - Nistain Kune; Nasrun Pakaya (Universitas Negeri Gorontalo, 2023)
Background: Stroke is a disturbance of the function of the nervous system that occurs suddenly due to problems with blood circulation in the brain. The purposed of this literature study is to synthesize evidence or literature about the Effect of Range Of Motion (ROM) on Muscle Strength in Stroke Patients. Method: This literature study applied the PICOT framework with the Google Scholar database, research gate, and PUBMED. Results: Show a correlation between Range of Motion (ROM) and Muscle Strength in Stroke Patients. In addition, ROM also increases the range of motion of joints in stroke patients. Conclusion: From this literature review, it can be concluded that 66.6% of research shows a correlation between ROM and muscle strength in stroke patients. In addition, about 33.3% of research shows that ROM therapy can increase the range of motion of joints in stroke sufferers.